The Issue of Papua, Between Two Interests of Indonesia and the US - Welly Puji Ginanjar; Yoedhi Swastanto; Priyanto; Beni Rudiawan (UNIVERSITAS PGRI YOGYAKARTA, 2020)
Abstract In the eastern part of the Republic of Indonesia, Papua has still considered a land of political and socio-economic conflict despite the richness of gold and uniqueness. Since the integration of Papua into Indonesia, the conflict still occurred and led to the separatism issue. Many have perceptions that there is a foreign state actor behind the issue. The role of the Indonesian government to overcome the conflicts in Papua is still questionable. In addition, the US with Freeport seems to be another issue that possibly has a linkage to several problems that occurred in the land. According to that perception, by taking a literature study, the writing will briefly explore Indonesia's role in dealing with the conflict and the US interest in Papua. Keywords: Papua, Indonesia, the US